On thin ice: Assembling a resilient service hub. Issue 3 (23rd April 2018) - Evans, Joshua; Collins, Damian; Chai, Cher‐Ann
Abstract : Inner‐city service hubs are vital spaces of survival for homeless populations. They are also vulnerable to gentrification‐induced displacement, putting the populations they serve at increased risk. This paper contributes to recent work on the resilience of inner‐city service hubs through a case study of Edmonton, Canada. Specifically, we theorise the assemblage‐like qualities of Edmonton's service hub, in the context of a major urban redevelopment project. As a heterogeneous grouping of different spaces of care, service hubs lend themselves well to assemblage thinking. Viewed from this vantage point, service hubs can been seen as relational achievements, assembled through articulations among voluntary sector, private and government organisations. We demonstrate how these articulations express multiple practices, ideals and values and add to the spatial resilience of the service hub in historically and spatially contingent ways.